Examining the Necessity of Reflective Module: Literacy Numeracy Skill of Students Elementary School - Yeni Rakhmawati; Ali Mustadi (STAI Hubbulwathan Duri, 2021)
The research aims to describe the need for reflective modules in building literacy skills of primary school students. The research used a quantitative descriptive method. The population was the fifth-grade primary school students that implement the 2013 curriculum with A accreditation—the data collection technique used non-test with observation instruments, questionnaires, interview guidelines, and literature review. The sample was taken using a purposive random sampling technique. The sample in this study was 126 students. The results showed that students and teachers need a reflective module to build numeracy literacy. The reflective module has the potential to build numeracy literacy skills. Literacy skill is closely related to reflective thinking processes, in which reflective thinking is a critical thinking process for making an assessment. Self-assessment aims to measure the extent of an individual's abilities to encourage the individual to develop self-potential.